A low-profile, wideband, circularly polarized, slotted, U-shaped textile antenna for W-BAN applications - Rishabh Kumar Baudh; Mahendra Kumar; Sonal Sahu; Manoj Singh Parihar; Dinesh Kumar V (ETRI Journal)
We propose a compact, wideband, U-shaped, circularly polarized textileantenna (UCPTA) resonating at 2.45 GHz for wireless body area network(W-BAN) applications. The radiator of the antenna is printed on the top of thesubstrate (size of 53:3 59:8 1 mm 3 ; 0:43λ 0:48λ 0:0081λ) and has a fullground plane on the other side. The proposed antenna’s substrate consists of asingle layer of denim (ϵr ¼ 1:7), and conductive copper tape was used to fabri-cate the patch. The antenna has a low-profile design that is suitable for wear-able applications. A small slot was introduced at the center of the U-shapedpatch to enhance the 3 dB axial ratio bandwidth (ARBW) up to 55.17%. Theproposed antenna radiates with a 10 dB return loss (RL), impedance band-width (IBW) of 64.40%, and a simulated gain of 5.1 dBi. The wearable textileantenna with broadside radiation response is appropriate for off-body commu-nications. The prototype of UCPTA is fabricated for experimental validation.The measured results for the fabricated antenna were in good agreement withthe simulated results. Further, it has been demonstrated that the antenna’sperformance is stable during structural deformation and human body loading.This textile antenna covers an ARBW in the frequency band of 2.1 GHz–3.72GHz and has a broad IBW (2 GHz–3.9 GHz) for LTE (2.17 GHz), MBAN (2.360GHz–2.4 GHz), WPAN (2.395 GHz–2.4 GHz), and WLAN (2.4 GHz–2.482GHz) applications.